CULTURAL EDUCATION AS AN EFFORT TO PREVENT RELIGIOUS-BASED RADICALISM ON SOCIAL MEDIA IN INDONESIA - Hafidzi, Anwar (Institut Agama Islam Negeri (IAIN) Manado, 2020)
This research begins with an understanding of the endemic radicalism of society, not only of the real world, but also of various online social media. This study showed that the avoidance of online radicalism can be stopped as soon as possible by accusing those influenced by the radical radicality of a secular religious approach. The methods used must be assisted in order to achieve balanced understanding (wasathiyah) under the different environmental conditions of the culture through recognizing the meaning of religion. The research tool used is primarily library work and the journal writings by Abu Rokhmad, a terrorist and radicalise specialist. The results of this study are that an approach that supports inclusive ism will avoid the awareness of radicalization through a heart-to-heart approach. This study also shows that radical actors will never cease to argue dramatically until they are able to grasp different views from Islamic law, culture, and families.Keywords: radicalism, deradicalization, multiculturalism, culture, religion, moderate.Penelitian ini berawal dari paham radikalisme yang telah mewabah di masyarakat, bukan hanya di dunia nyata, bahkan sudah menyusup di berbagai media sosial online. Penelitian ini menemukan bahwa cara menangkal radikalisme online dapat dilakukan pencegahan sedini mungkin melalui pendekatan konseling religius multikultural terhadap mereka yang terkena paham radikal radikal. Diantara teknik yang digunakan adalah melalui pemahaman tentang konsep agama juga perlu digalakkan agar memunculkan pemahaman yang moderat (wasathiyah) diberbagai keadaan lingkungan masyarakat. Metode yang digunakan untuk penelitian ini adalah library research dengan sumber utama adalah karya dan jurnal karya Abu Rokhmad seorang pakar dalam masalah terorisme dan radikalisme. Temuan penelitian ini adalah paham radikalisasi itu dapat dihentikan dengan pendekatan hati ke hati dengan mengedepankan budaya yang multikultural. Kajian ini juga membuktikan bahwa pelaku paham radikal tidak akan pernah berhenti memberikan argumen radikal kecuali mampu memahami perbedaan pendapat yang bersumber dari syariat Islam, lingkungan sosial, dan keluarga.Kata kunci: radikalisme, deradikalisasi, multikultural, budaya, agama, moderat.